TRANSPORT ANALYSIS OF NEON–COPPER PLASMA: POWER, ELASTIC/INELASTIC LOSSES, ENERGY CHARACTERISTICS AND TOTAL IONIZATION FREQUENCY - Fawzi, Msbah A. A.; Gatea , Ali J. (Antis-Publisher, 2026)
Objective: This study introduces a model and examines the transport parameters of a neon–copper plasma mixture, emphasising energy and power characteristics, along with the effects of both elastic and inelastic power losses. Method: The researchers utilise theoretical and computational methodologies, predominantly employing the Boltzmann equation to examine the distribution of electrons and ions within the plasma, and the equation is solved using numerical methods, which give a detailed look at how collisions affect power losses and help us better understand how energy moves through the plasma. Results: The study examines two principal factors: the diminished electric field (E/N), which varies from 1 to 20 Td, and the influence of fluctuating copper concentrations, ranging from 0.001 to 0.5 mol, on electron-related metrics, including power, elastic and inelastic power losses, and energy distribution, the analysis gives useful information about how these parameters change when the electric field and copper concentration change, and the results also show how elastic and inelastic processes work together and how they affect the plasma's power use and energy properties. Novelty: This study is pertinent to numerous applications, encompassing nanomaterial synthesis, metal surface treatment, plasma discharge technologies, light and laser generation, gas processing and pollutant elimination, and the advancement of sophisticated plasma-based electronic devices, providing a clear picture of how to predict and improve plasma performance in mixed-gas environments by accounting for the effects of electric fields and changing gas concentrations.